HUBUNGAN KAUSALITAS ANTARA NILAI TUKAR DAN INFLASI DI INDONESIA SELAMA PERIODE 2001 – 2010 - Bobby Yuga Utama; Birgitta Dian Saraswati (Optimum: Jurnal Ekonomi dan Pembangunan, 2011)
Indonesia is a small open economy, and has a monetary policy strategy of targeting inflation in consumer prices. In this paper, we look at the evidence from the Indonesia on inflation behaviour, and examine the propositions from several theoretical models about inflation dynamics in an open economy, focussing in particular on the hypothesised connections between the exchange rate and consumer price inflation.The objective of this research is to find out whether the relationship between inflation and exchange rate in Indonesia data during the period of 2001-2010. The method of analysis used in the study is Granger Causality Model to examine the interaction between inflation and the exchange rate in the Indonesia. The results show that the Granger causality between inflation and the exchange rate is bidirectional.